Economic Geography and the Irish Border: A Market Access Approach - Fernihough, Alan (Statistical and Social Inquiry Society of Ireland, 2024)
This paper examines the economic impact of Ireland’s partition, assessing market access losses using detailed geospatial data and multimodal transport network analysis. The study reveals that partition significantly reduced market access on both sides of the border, contributing to population decline. Districts closest to the border were the most affected, with estimated population figures being approximately 10 per cent lower than they would have been without the border. This negative impact has persisted, remaining evident despite the reduction of many physical border barriers. A counterfactual analysis suggests that absent the border, the current populations of the Republic of Ireland and Northern Ireland would have been 3 per cent and 5 per cent higher, respectively. These findings illustrate the persistent role of political borders in shaping regional economic activity.
read before the Society, 25th January 2024
Keywords: Economic Geography; Irish Border; Market Access; Economic History of Ireland; 314.15